The craft and science of game design : a video game designer's manual - O'Connor, Phil (Video game designer) (Boca Raton : CRC Press, 2021)
The Craft and Science of Game Design: A Video Game Designer's Manual goes into the nuts and bolts of video game development from the perspective of a veteran designer with more than 20 years of experience in the industry. It covers the psychology and biology of why people play games and goes in depth on the techniques and tricks professional game designers use to be successful in game development. If you are looking to make a career in video games, or are already in the industry, the insights and hard-earned lessons contained in this book are sure to be useful at all levels of the profession. Originally from Canada, Phil O'Connor has been making video games all over the world since 1997. Phil has worked at some of the industry's largest studios on some of the biggest projects, including Far Cry 3 and Rainbow Six Siege. With credits on nearly 20 games, Phil has shared in this book some of the less-known details of being a game designer in today's video game industry, along with a breakdown of some of the skills to help professional designers shine.
OCLC-licensed vendor bibliographic record.
Keywords: Video games -- Design -- Vocational guidance; Video games -- Programming -- Vocational guidance; Video games industry; COMPUTERS / Computer Science; GAMES / Video & Electronic